A Simple and Rapid Turn On ESIPT Fluorescent Probe for Colorimetric and Ratiometric Detection of Biothiols in Living Cells - Yi Wang (Nature Portfolio, 2017)
Abstract Biothiols, such as cysteine (Cys), homocysteine (Hcy), and glutathione (GSH), play a key role in an extensive range of physiological processes and biological functions. Therefore, the selective and sensitive detection of intracellular thiols is important for revealing cellular function. In this study, ethyl 2-(4-(acryloyloxy)-3-formylphenyl)-4-methylthiazole-5-carboxylate (NL-AC) was designed and synthesized as a colorimetric and ratiometric fluorescent probe that can be utilized to rapidly, sensitively and selectively detect biothiols in physiological media. The fluorescence intensity of this probe using the three target biothiols at a concentration of 20 equiv. of the probe increased by approximately 6~10-fold in comparison to that without the biothiols in aqueous solution. The limits of detection (LOD) for Cys, Hcy and GSH were 0.156, 0.185, and 1.838 μM, respectively. In addition, both 1H-NMR and MS analyses suggested the mechanism of fluorescence sensing to be excited-state intramolecular proton transfer (ESIPT). The novel colorimetric and ratiometric probe is structurally simple and offers detection within 20 min. Furthermore, this probe can be successfully applied in bioimaging. The results indicate high application potential in analytical chemistry and diagnostics.